The Flouting of Gricean Maxims Found in the TV Series Mom - Nurmalia Ayu Kharismawanti; Amin Basuki (Universitas Gadjah Mada, 2020)
This research discusses the flouting of Gricean maxims done by all the characters in the TV series Mom in the first 10 episodes in season 1. This research aims to identify and to classify the flouting of Gricean maxims according to Cutting’s classification and the most used method of flouting. The quantitative and qualitative methods are used as data analysis instruments. It is discovered that there are 99 flouting, with 59.6% (59 cases) among which is flouting of maxim of quality, 18.2% (18 cases) is flouting of maxim of quantity, 13.1% (13 cases) is flouting of maxim of relation, and 9.1% (9 cases) is flouting of maxim of manner. The characters in Mom tend to flout the maxims by using metaphors, being irrelevant, using irony or sarcasm, using hyperbole, or being ambiguous or obscure. The analysis shows that the characters flouted the maxims for several reasons, with the most frequent one is to offend or to hurt the hearer and to convince the hearer.